EVOLUSI KOMPUTER, KINERJA KOMPUTER DAN INTERCONNECTION NETWORKS DALAM PERKEMBANGAN DUNIA TEKNOLOGI INFORMATIKA - Sinaga, Dimpo (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2015)
Informtika Engineering Department should be able to make plans in accordance with the Program in accordance with the wish to make. Berdasrkan logic systematically created a very complex logical thinking is required, whereas if the program that we make must tratur and directed, it is quite a Progremer that make the program shall have a mathematical logic. In addition to thinking of efficient human resources, as a program must also determine what logical programming language that is suitable for use or do not even need to use a programming language, because it uses a programming language that requires great thought just to make simple and will not even static efficiency of In terms of the program.